Noncontact Monitoring and Imaging of the Operation and Performance of Thin‐Film Field‐Effect Transistors - Kwangsik Jeong; Dong yeob Shin; Ji‐Min Park; Dong‐Joon Yi; Hyunmin Hong; Hyun‐Suk Kim; Kwun‐Bum Chung (Advanced Science)
Abstract In this study, the first noncontact and non‐destructive methodology is developed for monitoring and imaging the operation and performance of thin‐film field‐effect transistors (TFTs) using second‐harmonic generation (SHG) imaging. By analyzing the SHG signal intensity, which is directly related to the electric field at the interface between the semiconductor channel and gate insulator, critical electrical parameters such as the threshold voltage (VTH) and flat‐band voltage (VFB) are successfully determined. These findings demonstrate a strong correlation between SHG signals and VTH and VFB in InGaZnO TFTs under various process conditions. Notably, the method achieves an unprecedented resolution of ΔVFB below 100 mV in assessing electrical properties through SHG measurements, surpassing conventional spectroscopy techniques. Furthermore, a system is developed to monitor and image the TFT array operation and performance, enabling us to distinguish between pass and fail devices and measure the VTH distribution based on the SHG intensity. This approach facilitates early failure detection and supports efficient curing during manufacturing, thereby marking significant advancements in TFT technology and quality control processes.